2018
DOI: 10.1186/s10020-018-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of down-regulated microRNA-31 on intestinal barrier dysfunction through inhibition of NF-κB/HIF-1α pathway by binding to HMOX1 in rats with sepsis

Abstract: BackgroundIntestinal barrier dysfunction is a significant clinical problem, commonly developing in a variety of acute or chronic pathological conditions. Herein, we evaluate the effect of microRNA-31 (miR-31) on intestinal barrier dysfunction through NF-κB/HIF-1α pathway by targeting HMOX1 in rats with sepsis.MethodsMale Sprague-Dawley rats were collected and divided into the sham group, and the cecum ligation and perforation group which was subdivided after CACO-2 cell transfection of different mimic, inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…We reasoned that hypoxia and inflammation may reduce ZO-1 expression through different intracellular signaling pathway, and that propofol may have different effect on these pathways. Hif-1α has been reported to be involved in occludin expression [33]. In addition, the role of Hif-1α in tight junction damage has recently become evident [14].…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that hypoxia and inflammation may reduce ZO-1 expression through different intracellular signaling pathway, and that propofol may have different effect on these pathways. Hif-1α has been reported to be involved in occludin expression [33]. In addition, the role of Hif-1α in tight junction damage has recently become evident [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well reported that oxygen metabolic disorders and cascade amplification of inflammatory responses are dominant clinicopathological features in sepsis-induced ALI [20,21]. Accumulating evidence shows that inhibition of HIF-1α protects against intestinal barrier dysfunction in rats with sepsis [22]. In the development process of acute lung inflammatory damage induced by treatment with septic lymph, the expression level of HIF-1 α was induced and activated in rats [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hif-1α has been reported to be involved in occludin expression [ 32]. In addition, the role of Hif-1α in tight junction damage has recently become evident [ 14].…”
Section: Discussionmentioning
confidence: 99%